Pengaruh Organizational Justice Terhadap Employee Innovative Work Behavior Dengan Knowledge Sharing Sebagai Mediasi (Studi Kasus BPJS Ketenagakerjaan Kantor Cabang Pasuruan) - Priyanto, Teguh; Setyowati, Widhy; Sutanto, Himawan Arif (Magister Manajemen STIE Bank BPD Jateng, 2024)
This study aims to analyze the effect of organizational justice on employee innovative work behavior with knowledge sharing as mediation. The population in this study were employees of BPJS Ketenagakerjaan Pasuruan Branch Office as many as 75 employees. The sampling technique used in this study is saturated sampling or census. Data analysis was performed with SEM-PLS. The results showed that organizational justice and knowledge sharing had a positive and significant effect on employee innovative work behavior of BPJS Employment Branch Office Pasuruan employees. Organizational justice has a positive and significant effect on knowledge sharing. Knowledge sharing mediates the relationship between organizational justice and employee innovative work behavior